On the role of chirality flips for the muon magnetic moment and its relation to the muon mass - Stöckinger, Dominik; Stöckinger-Kim, Hyejung (Frontiers in Physics, 2022)
The muon mass and the anomalous magnetic moment a_μ are quantities which require chirality flips, i.e. transitions between left- and right-handed muons. Muon chirality flips are connected to electroweak symmetry breaking and Yukawa couplings. Scenarios for physics beyond the Standard Model motivated by the quest to understand electroweak symmetry breaking and/or the origin of flavour often introduce new sources of chirality flips; they hence provide potentially large contributions to a_μ, and the current a_μ measurement provides relevant constraints on such scenarios. This connection between a_μ, chirality flips, and the muon mass generation mechanism is important and underlies much of the current research on a_μ. The present article provides a brief pedagogical introduction to this role of chirality flips and an overview of general relationships. The general statements are illustrated with several concrete models involving e.g. leptoquarks and supersymmetry.